A review of the genus Pempheris (Teleostei, Pempheridae) found in Japan and Taiwan - Keita Koeda; Manabu Bessho-Uehara (ZooKeys)
Species of the genus Pempheris Cuvier, 1829 (Pempheridae) from Japan and Taiwan are taxonomically reviewed based on morphology supported by molecular phylogenetic analysis. Ten species are recognized from these countries: Pempheris adusta Bleeker, 1855, Pempheris familia Koeda & Motomura, 2017, Pempheris japonica Döderlein, 1883, Pempheris nyctereutes Jordan & Evermann, 1902, Pempheris oualensis Cuvier, 1831, Pempheris sasakii Jordan & Hubbs, 1925, Pempheris schwenkii Bleeker, 1877, Pempheris ufuagari Koeda, Yoshino & Tachihara, 2013, Pempheris vanicolensis Cuvier, 1831, Pempheris xanthoptera Tominaga, 1963. Nine of them are distributed in Japan, and five of them in Taiwan. Pempheris sasakii and P. xanthoptera, nominal species that have been regarded as invalid are revalidated, redescribed with diagnoses based on examinations of the holotypes and the specimens collected from Japan. Pempheris sasakii is morphologically similar to P. nyctereutes and has been thought to be a senior synonym of the latter, but the comparison of the holotypes and non-types of both species revealed that the former species is distinguishable from the latter species in having fewer counts of body scales, also genetically supported with a 3.1% mitochondrial DNA sequence divergence. Pempheris xanthoptera is similar to P. schwenkii, but the coloration of their caudal fins is different, and the genetic analysis supported the difference. The distributions of all species of the genus Pempheris in Japanese waters are also described, based on the specimen localities from literature and new material herein.